Synthesis and characterization of zirconium oxide modified with phosphate ion (Superficies y Vacío, 2013)
In this work was conducted the decomposition reaction of 2-propanol to obtain propylene using phosphated zirconia as catalyst. The synthesis of Zr(OH)4 was carried out by the sol-gel method. The materials were modified with phosphoric acid and calcined at 400°C. Characterization tests included X-ray diffraction, nitrogen physisorption, infrared spectroscopy and scanning electron microscopy. The results indicated that were obtained solids with tetragonal structure and the addition of phosphate ion increased the specific surface area in the materials. On the other hand, reaction tests revealed that the phosphated catalysts had higher catalytic activity and the active sites dominant were acid sites.